IN SEARCH OF THE NON-EXISTING SITCH: DECONSTRUCTION OF A HISTORIOGRAPHICAL MYTH (Південний архів (історичні науки), 2025)
The purpose of the article is to verify the existing scientific hypotheses regarding the location of the so-called Bazavlutska Sich and to refute the historiographical construct of its existence as a stationary fortified military-administrative centre based on a comprehensive analysis of historical sources, cartographic materials and satellite images using modern GIS technologies.Research methods used are both general scientific (analysis and synthesis) and special historical methods: cartographic, source study and geographic information systems. Results. The author refutes the idea of the existence of the Bazavlutska Sich as a stable, stationary fortification of the Zaporozhian Cossacks in Velykyi Luh during 1593–1638, which is established in historiography. Based on the analysis of a wide range of written sources, historiography of the XVIII–XXI centuries, cartographic materials and satellite images using GIS technologies, it is established that The Bazavlutska Sich is a historiographical construct formed in the second half of the nineteenth century under the influence of a romantic interpretation of the past and an attempt to fill in the gaps in sources without proper verification.Conclusions. As a result of the study, the assumptions about the location of the so-called Bazavlutska Sich were verified. The analysis has revealed the absence of a stable tradition of locating this fortification in historical sources. The main narratives that shaped the perception of the Bazavlutska Sich during the nineteenth century are based, in fact, only on the testimony of E. Lassota in 1593. The application of the GIS method allowed us to compare the imaginary cartographic image of the Sich with the real landscapes of the Velykyi Luh, discovered after the draining of the Kakhovka Reservoir as a result of the hydroelectric power plant explosion in 2023.The study found that in 1593–1638, the Cossacks did indeed use the territory of Velykyi Luh as a temporary base. However, there is no source evidence to suggest the existence of a permanent, stationary fortification that would meet the characteristics of the Sich as a Cossack political, administrative, and military centre.
Keywords: Bazavlutska Sich, Velykyi Luh, GIS analysis, history of Zaporizhzhia Cossacks, Cossack fortifications